Peningkatan Hasil Belajar IPA melalui Media Audio Visual dengan Model Pembelajaran Cooperative Script pada Siswa Kelas VIII SMP Negeri 1 Ceper - Agustina, Lina (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
This aims of Classroom Action Research (PTK) study to determine the increase of science learning outcomes through audio visual media with Cooperative Script learning model on the students of grade VIII SMP Negeri 1 Ceper. The subjects of the study were the students number 30 of class VIII A. This research was conducted through two cycles, namely cycle I and cycle II. Each cycle took four stages: planning, action execution, and evaluation or reflection. This research was conducted by involving researchers who act as teachers and assisted by science teachers as observers of student and teacher activities. The results showed that there was an increase of each cycle. In the pre test the average grade of 65.13 and who complete the study of 9 students or 30%. After learning through audio visual media with Cooperative Script learning model in the first cycle, the average score of 72.16, students finished learning was 18 or 60%. In the cycle II the average score of students is 81.2 and 26 studentsfinished learning was or 86.66%. The results of learning science through audio visual media with Cooperative Script learning model on the students of class VIII A showed a significant increase at SMP Negeri 1 Ceper.